The Effects of Resveratrol on Hyperoxia-induced Lung Injury in Neonatal Rats - Özmert M.A. Özdemir; Ersin Gözkeser; Ferda Bir; Çiğdem Yenisey (Elsevier, 2014)
Bronchopulmonary dysplasia (BPD) is a chronic lung disease that causes significant morbidity and mortality in premature infants. Inflammation and oxidative injury play an important role in the pathogenesis of BPD. Resveratrol is an antioxidant and anti-inflammatory agent. In this study, the histopathological and biochemical effects of resveratrol on a hyperoxia-induced lung injury model in newborn rats were investigated. Methods: The experiment was performed on newborn rat pups from the 3rd to 13th postnatal day and they were randomly divided into four groups: Group 1 (air-exposed + saline, n = 10), Group 2 (air-exposed + resveratrol, n = 11), Group 3 (hyperoxia-exposed + saline, n = 6) and Group 4 (hyperoxia-exposed + resveratrol, n = 7). Resveratrol was administered (30 mg/kg/day) intraperitoneally. The histopathological effects of resveratrol on lung tissue were assessed by alveolar surface area, fibrosis, and smooth muscle actin (SMA) score, and the biochemical effects on lung tissue were assessed by glutathione (GSH), superoxide dismutase (SOD), nitric oxide (NO), tumor necrosis factor-α (TNF-α), and nuclear factor kappa B (NF-κB) levels. Results: The alveolar surface area, fibrosis, SMA score, and NO levels were found to be significantly higher in Group 3 compared with Group 1 (p < 0.05). In addition, it was found that resveratrol treatment significantly reduced the SMA score and the NO and TNF-α levels, and increased the GSH and SOD levels in the hyperoxia group (p < 0.05). Conclusion: This experimental study showed that oxidative stress and NO contributed to the pathogenesis of hyperoxia-induced lung injury, and that resveratrol had a preventive effect on hyperoxic lung injury through its anti-inflammatory and antioxidant properties.